2005
DOI: 10.1128/aem.71.10.5935-5942.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Small Eukaryotes in Lakes Differing by Their Trophic Status

Abstract: Small eukaryotes, cells with a diameter of less than 5 m, are fundamental components of lacustrine planktonic systems. In this study, small-eukaryote diversity was determined by sequencing cloned 18S rRNA genes in three libraries from lakes of differing trophic status in the Massif Central, France: the oligotrophic Lake Godivelle, the oligomesotrophic Lake Pavin, and the eutrophic Lake Aydat. This analysis shows that the least diversified library was in the eutrophic lake (12 operational taxonomic units [OTUs]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
230
6
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(253 citation statements)
references
References 58 publications
13
230
6
4
Order By: Relevance
“…However, the diversity indices for nirS gene in our study were lower than those in a flooded paddy field reported by Yoshida et al (2009). There are substantial evidences that the diversity and composition of soil bacterial communities can be influenced by a wide range of biotic and abiotic factors including vegetation, trophic status, salinity, soil pH and heavy metals (McArthur et al, 1988;Lefranc et al, 2005;Lozupone and Knight, 2007;Fierer and Jackson, 2006;Gans et al, 2005).…”
Section: Shifts In Diversity and Composition Of The Denitrifying Commcontrasting
confidence: 84%
“…However, the diversity indices for nirS gene in our study were lower than those in a flooded paddy field reported by Yoshida et al (2009). There are substantial evidences that the diversity and composition of soil bacterial communities can be influenced by a wide range of biotic and abiotic factors including vegetation, trophic status, salinity, soil pH and heavy metals (McArthur et al, 1988;Lefranc et al, 2005;Lozupone and Knight, 2007;Fierer and Jackson, 2006;Gans et al, 2005).…”
Section: Shifts In Diversity and Composition Of The Denitrifying Commcontrasting
confidence: 84%
“…In this study, both parametric rarefaction curves and nonparametric richness estimators revealed a higher diversity of picoeukaryotes in the oligomesotrophic MB than in the eutrophic TH (Table 3, Figure 2). This finding is in good agreement with that of Lefranc et al (2005) and provides further evidence on the classic unimodal diversity-productivity relationship.…”
Section: Diversity Of the Picoeukaryotic Assemblagessupporting
confidence: 80%
“…Recent analysis of a global data set has revealed a similar pattern between marine phytoplankton diversity and phytoplankton biomass (Irigoien et al, 2004). Lefranc et al (2005) used the cloning and sequencing method to study the genetic diversity of small eukaryotes (o5 mm) in three lakes in France and reported a higher diversity in the oligomesotrophic lake than in the oligotrophic and eutrophic lakes. In this study, both parametric rarefaction curves and nonparametric richness estimators revealed a higher diversity of picoeukaryotes in the oligomesotrophic MB than in the eutrophic TH (Table 3, Figure 2).…”
Section: Diversity Of the Picoeukaryotic Assemblagesmentioning
confidence: 99%
“…1). The LKM11 (AJ130849) sequence branched within this group, as well as other environmental sequences classified in other studies as related to it (Lefranc et al 2005;Luo et al 2005;Šlapeta et al 2005;Van Hannen et al 1999). Given the high statistical support in our phylogenetic analyses for the Rozella/LKM11 clade, we propose here to name this group ''Rozellida'', in reference to the genus Rozella.…”
Section: Resultsmentioning
confidence: 52%